CORRELATION BETWEEN KNEE OSTEOARTHRITIS (OA) GRADE AND BODY MASS INDEX (BMI) IN OUTPATIENTS OF ORTHOPAEDIC AND TRAUMATOLOGY DEPARTMENT RSUD DR. SOETOMO - Lukas Widhiyanto; Andre Triadi Desnantyo; Lilik Djuari; Maynura Kharismansha (Journal Orthopaedi and Traumatology Surabaya, 2017)
Osteoarthritis (OA) is the number eight disease causes Years of Disability in developing countries. OA worsen life quality, from movement limitation until inability to perform normal daily routines. Obesity is one of the risk factor of OA. The doubles increasing trend of obesity from 1980, might possibly causes the escalation of OA case. However, there is still no study that explains the correlation between OA grade, especially knee OA, with Body Mass Index (BMI). The purpose of this study was to determine whether there is correlation between knee osteoarthritis (OA) grade with Body Mass Index (BMI) in outpatients of Orthopaedic and Traumatology department RSUD Dr. Soetomo. This study was cross-sectional study with analitical observational design and survey was the method to determine whether there is correlation between knee OA grade and BMI. Height and weight measurement and also knee x-ray reading were performed to determine the BMI and knee OA grade. The BMI categories that were used were based on standard from Health Department of Republic of Indonesia, while the grading system that were used were based on Kellgren-Lawrence’s grading system. Populations in this study were taken from the outpatients of Orthopaedic and Traumatology Department RSUD Dr. Soetomo during August until November 2015. After statistic test using Spearman correlation test was done, the result was p=0,822. It can be concluded that there was no significant correlation between knee OA grade and BMI. Furthermore, knee OA grade was not affected by BMI only, but also other risk factors as well.